A national health impact assessment of achieving tree canopy goals in US urban areas - Michelle C. Kondo; Tamara Iungman; Evelise Pereira Barboza; Dexter H. Locke; Ray Yeager; Dustin Fry; Ava-Clare Steed; Marcia Pescador Jiménez; David Rojas-Rueda; Mark Nieuwenhuijsen (Environmental Research, 2026)

The effect of place-based nature interventions on human health: A systematic review - Dustin Fry; Jalayna Antoine; Kylan Simpson; Ava-Clare Steed; Charles C. Branas; Mark Nieuwenhuijsen; Kristin Mmari; Michelle C. Kondo (Environmental Research, 2026)

Measuring Neighborhood Order and Disorder: a Rapid Literature Review - Steeve Ndjila; Gina S. Lovasi; Dustin Fry; Amélia A. Friche (Current Environmental Health Reports, 2019)
Purpose of Review Neighborhood disorder has received attention as a determinant of health in urban contexts, through pathways that include psychosocial stress, perceived safety, and physical activity. This review provides a summary of data collection methods, descriptive terms, and specific items employed to assess neighborhood disorder/order. Recent Findings The proliferation of methods and terminology employed in measuring neighborhood disorder (or neighborhood order) noted over the past two decades has made related studies increasingly difficult to compare. Following a search of peer-reviewed articles published from January 1998 to May 2018, this rapid literature review identified 18 studies that described neighborhood environments, yielding 23 broad terms related to neighborhood disorder/order, and a total of 74 distinct measurable items. Summary A majority of neighborhood disorder/order measurements were assessed using primary data collection, often relying on resident self-report or investigatory observations conducted in person or using stored images for virtual audits. Items were balanced across signs of order or disorder, and further classification was proposed based on whether items were physically observable and relatively stable over time.